Tax Planning, Institutional Ownership, and Earnings Management: A Moderating Role: Dampak Perencanaan Pajak dan Beban Pajak terhadap Pengelolaan Laba: Peran Moderasi Kepemilikan Institusional - Nadia Qonata Nisa'; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2022)
This study employs a quantitative approach, employing Moderated Regression Analysis through the SPSS program, to investigate the influence of tax planning, deferred tax assets, and deferred tax expense on earnings management. The study also examines the moderating effect of institutional ownership on this relationship. The findings reveal a significant association between tax planning, tax burden, and earnings management when considering institutional ownership as a moderating factor. However, no significant effect of deferred tax assets on earnings management was observed when institutional ownership was taken into account. These results contribute to the existing literature, providing reference material for future research on the interplay between tax planning, deferred tax assets, deferred tax expense, earnings management, and institutional ownership. The implications of these findings highlight the importance of institutional ownership as a moderating variable in the relationship between tax-related factors and earnings management practices. Highlights: Tax planning and earnings management: This study examines the relationship between tax planning strategies employed by companies and their impact on earnings management practices. It highlights the potential influence of tax-related decisions on financial reporting outcomes. Moderating role of institutional ownership: The study investigates the role of institutional ownership as a moderating variable in the relationship between tax planning, tax burden, and earnings management. It sheds light on how institutional ownership can affect the behavior and practices of companies in managing their earnings. Implications for future research: The findings of this study contribute to the existing literature on earnings management and provide a reference for further research. It underscores the importance of considering institutional ownership as a relevant factor in analyzing the effects of tax-related factors on earnings management practices. Keywords: tax planning, tax burden, earnings management, institutional ownership, moderating role.